Additive manufacture of complex 3D Au-containing nanocomposites by simultaneous two-photon polymerisation and photoreduction. Issue 1 (December 2017) - Hu, Qin; Sun, Xue-Zhong; Parmenter, Christopher; Fay, Michael; Smith, Emily; Rance, Graham; He, Yinfeng; Zhang, Fan; Liu, Yaan; Irvine, Derek; Tuck, Christopher; Hague, Richard; et al.
Abstract The fabrication of complex three-dimensional gold-containing nanocomposite structures by simultaneous two-photon polymerisation and photoreduction is demonstrated. Increased salt delivers reduced feature sizes down to line widths as small as 78 nm, a level of structural intricacy that represents a significant advance in fabrication complexity. The development of a general methodology to efficiently mix pentaerythritol triacrylate (PETA) with gold chloride hydrate (HAuCl4 ∙3H2 O) is reported, where the gold salt concentration is adjustable on demand from zero to 20 wt%. For the first-time 7-Diethylamino-3-thenoylcoumarin (DETC) is used as the photoinitiator. Only 0.5 wt% of DETC was required to promote both polymerisation and photoreduction of up to 20 wt% of gold salt. This efficiency is the highest reported for Au-containing composite fabrication by two-photon lithography. Transmission Electron Microscopy (TEM) analysis confirmed the presence of small metallic nanoparticles (5.4 ± 1.4 nm for long axis / 3.7 ± 0.9 nm for short axis) embedded within the polymer matrix, whilst X-ray Photoelectron Spectroscopy (XPS) confirmed that they exist in the zero valent oxidation state. UV-vis spectroscopy defined that they exhibit the property of localised surface plasmon resonance (LSPR). The capability demonstrated in this study opens up new avenues for a range of applications, including plasmonics, metamaterials, flexible electronics and biosensors.